Gentrifying a Superfund Site: Why Gowanus, Brooklyn is Becoming a Real Estate Hot Spot - Krisel, Rebecca Salima (Consilience, 2015)
This feature length article tells the story of Gowanus, a Brooklyn neighborhood on the Gowanus Canal, haunted by the pollutants of its industrial past. that rests along the banks of the Gowanus Canal. The Environmental Protection Agency recognized the latter Gowanus Canal as a Superfund cleanup site in March 2010. Yet , Gowanus is experiencing an economic and cultural revival. What was historically a booming manufacturing area with active warehouses spilling their waste into the Gowanus Canal is now an industrial wasteland site where middle to upper class families, seeking to purchase organic foods, are willing to relocate and settle down. As of December 2014, a two-bedroom condo boasting waterfront views and located just one block away from the Gowanus Canal on Carroll Street in between Nevins Street and Third Avenue, was selling priced atfor 1,549,000. The average price per square foot for homes in Gowanus is 50 percent higher than the rest of Brooklyn. This story links issues of sustainable development and current urban housing needs in New York City. My research rested primarily on interviews with subjects who have specific expertise in the changes of the neighborhood. I was fortunate to speak with a real estate agent who specializes in Gowanus, a representative at an affordable housing advocacy group working on development in Gowanus, two separate families who moved to the area when they started began having children, and a life-long resident of 27 years. I also attended two community meetings relating to the sustainable development of Gowanus in addition to speaking with some old and new shop dwellers.